De l’obsolescence dans la médiation - Véronique Dagues (Recherches en didactique des langues et des cultures)
If it is generally understood that “the learner” who is “at the center of learning” should be considered to be the main “actor” and “vector” of learning, little attention has been paid to the “teacher” in the Communicative Approaches and Action oriented Perspectives supported by the Common European Framework of Reference for Languages. It would seem that the CEFL and DLE (didactics of foreign languages) have forgotten, depreciated or erased entirely the important role of the teacher from didactic memories. Consequently, a reconfiguration of the roles and places of each figure in the didactic triangle would seem to have occurred, such that each line (representing the learner, the language and the teacher) collapses into a single one. I argue that the best mediation comes from the teacher, not because he/she knows everything about everything, but because he/she knows more than those who believe they can learn everything by themselves. But if “the learner is thought of as a social actor with his own personal identity and learning a form of social mediation” (Dictionary of French didactic as foreign and second Language), one would neither be able to reduce the learner to a function nor assign the learner to the role of an actor without denying what the learner is above all else: a subject, capable of speech (Anderson).Is language reducible to a sort of machinery of which it is a question of learning the manipulations, uses, modes, and functions; a tool for knowing how to say, do and be and learn for learning’s sake, a form of transport, a vehicle-language? I claim that once one is able to speak in one’s mother tongue, one will be able to speak in a foreign language, or in mathematical, scientific, poetic or literary languages largely through one’s “desire” to learn them. The best person placed to transmit this desire is still the one who is inhabited by it. Perhaps one should reconsider the main vector of learning as something open to question when it comes to learning (and to the transmission of knowledge) in speakers. It could be that the coming Net Generation is expecting or hoping for something other than mere “ready-to-use” skills and actions.